If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4b + 64 = 2b + 68 Reorder the terms: 64 + 4b = 2b + 68 Reorder the terms: 64 + 4b = 68 + 2b Solving 64 + 4b = 68 + 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 64 + 4b + -2b = 68 + 2b + -2b Combine like terms: 4b + -2b = 2b 64 + 2b = 68 + 2b + -2b Combine like terms: 2b + -2b = 0 64 + 2b = 68 + 0 64 + 2b = 68 Add '-64' to each side of the equation. 64 + -64 + 2b = 68 + -64 Combine like terms: 64 + -64 = 0 0 + 2b = 68 + -64 2b = 68 + -64 Combine like terms: 68 + -64 = 4 2b = 4 Divide each side by '2'. b = 2 Simplifying b = 2
| 8n-n=-4+6n | | 7c-77=4c-35 | | -4x+4=11+2x-7x | | 9x+16y=7 | | 2/y-3=3/y | | 3q+6=6q | | 3+3(2-6)= | | -5+6x=x+10 | | 2s-48=s | | 2s+40=4s+28 | | x/3-=11 | | 3y=7x-9 | | 9x-12y+6=0 | | 3s-62=s | | 5p-60=p-4 | | n-8-1=-13 | | -5-7k+8k=0 | | x=2x-70 | | -12a-5b=27 | | 3z=z+26 | | r/320 | | 4n-2n+4=1+17 | | 4v-3+8=13 | | -1/2w-7/5=4/3 | | 3+3(2-6)squared= | | -8a-2a=-10 | | b+4=2b-3 | | -x-8=x+2 | | -4(5x-4)+3(4x+2)= | | 6n-3=3n-15 | | 2(2x+2)-3(x-4)= | | A/2=36 |